Downwardly Global Women, Work, and Citizenship in the Pakistani Diaspora - Ameeriar, Lalaie (Duke University Press, 2017)
In 'Downwardly Global' Lalaie Ameeriar examines the transnational labor migration of Pakistani women to Toronto. Despite being trained professionals in fields including engineering, law, medicine, and education, they experience high levels of unemployment and poverty. Rather than addressing this downward mobility as the result of bureaucratic failures, in practice their unemployment is treated as a problem of culture and racialized bodily difference. In Toronto, a city that prides itself on multicultural inclusion, women are subjected to two distinct cultural contexts revealing that integration in Canada represents not the erasure of all differences, but the celebration of some differences and the eradication of others. 'Downwardly Global' juxtaposes the experiences of these women.